Detection of Antimicrobial Phenotypes, β-Lactamase Encoding Genes and Class I Integrons in Salmonella Serovars Isolated from Broilers - Halawa, Marwa; Moawad, Amgad; Eldesouky, Ibrahim; Ramadan , Hazem (International Journal of Poultry Science, 2015)
This study was conducted to determine the occurrence, antimicrobial resistance profile, β-lactamase encoding genes and class I integrons (intI) of Salmonella serovars in broiler flocks. A total of 100 diseased chickens (5 samples per bird; cloacal swab, liver, gall bladder, spleen and intestinal content) were randomly selected from different broiler farms at Dakahliya and Kafrelsheikh Governorates, Egypt, during the period from September through December 2013. Conventional isolation and serotyping, antimicrobial resistance phenotyping, PCR identification of β-lactamase encoding genes and intI were performed. The culturing and serotyping identified 23 (23%) Salmonella isolates from diseased birds that belonged to 13 serotypes. The predominant serovars distinguished in this study were Salmonella Enteritidis, S. Typhimurium, S. Kentucky and S. Infantis that constituted 52.2% (12/23) of all isolates. By antimicrobial resistance testing, 87% (20/23) of isolates exhibited multidrug resistance (MDR; resistance to 5 or more antibiotics) mostly against vancomycin, oxacillin, amoxicillin, erythromycin and nalidixic acid. For 3rd generation cephalosporins, all the isolates were sensitive to cefoxitin and only 5 (21.7%) isolates displayed resistance to ceftriaxone and cefotaxime. Using PCR, all isolates were negative for blaSHV, blaCTX, blaCMY and blaOXA, while only 5 isolates (21.7%) harbored blaTEM (1080 bp). Variable amplicons with intI cassettes were detected by PCR from only 4 isolates (17.4%). Our findings highlighted the zoonotic potential of Salmonella in broilers with a possibility of antimicrobial resistance gene transmission to humans. Continuous surveillance is required to minimize the risk of human exposure to antimicrobial resistance pathogens from food producing animals.